Cypermethrin and Fenvalerate Induced Protein Alterations in Freshwater Crab Barytelphusa cunicularis (Westwood) - G.K. Kulkarni2, P.P. Joshi1* and (Recent Research in Science and Technology, 2011)
Cypermethrin and fenvalerate are two synthetic pyrethroid pesticides, commonly used in agriculture fields for the control of insects because of their high insecticidal activity and low mammalian toxicity. The mobilization of these pyrethroids from field to aquatic system induce lethal and sub lethal effects on non-target animals particularly crabs, which has high food value. In the present study, an attempt has been made to study the effect of cypermethrin and fenvalerate on protein content of different tissues like ovary, hepatopancreas, intestine, gill and thoracic muscle of the freshwater crab Barytelphusa cunicularis (Westwood). The crabs were exposed to sub lethal concentration (1/10th of 24 h LC50) of cypermethrin and fenvalerate for a period of ten days. The treatments of these pyrethroids brought about significant decrease in protein content in all tissues as compared to control. The maximum decrease was observed in hepatopancreas. The percent decrease of total protein content was in the order of: hepatopancreas > ovary > gill > intestine > muscle. The obtained results indicate that cypermethrin has more toxic effects than fenvalerate. The significance of these studies as bioindicator for assessing the toxicity and economic importance of the crab are discussed.